2020
DOI: 10.1002/pc.25815
|View full text |Cite
|
Sign up to set email alerts
|

Analytical approach to study the vibration of delaminated multi‐scale composite cylindrical shells

Abstract: In this study, the effect of carbon nano‐tubes (CNTs) and fiber carbons on vibration frequency of delaminated anti‐symmetric cross‐ply cylindrical shells is investigated. In this case, (CNTs) are added into polymer matrix of industrial composite. The mixture of rule and Halpin‐Tsai relation are used to obtain the effective materials of reinforced delaminated multi‐scale composite cylindrical shell. Based on Galerkine's method an approximate‐analytical solution is presented to predict the frequency vibration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…Viswanathan [ 20 ] studied the free vibration of the anti-symmetric cylindrical shell wall under the first-order shear deformation theory by the spline method, and analyzed the parameters of length, the number of circumferential nodes, the angle of the laminate, the number of laminates, the laminated material, and the boundary conditions of the anti-symmetric cylindrical shell. Baharali [ 21 ] studied the effects of carbon nanotubes (CNTs) and fiber carbon on the vibration frequency of anti-symmetric cylindrical shells, and evaluated the effects of carbon nanotube weight percentage and geometric parameters. Narwariya [ 22 , 23 ] conducted numerical studies on the free vibration and harmonic analysis of anti-symmetric laminates, and obtained the frequency-amplitude relationship of anti-symmetric anisotropic plates.…”
Section: Introductionmentioning
confidence: 99%
“…Viswanathan [ 20 ] studied the free vibration of the anti-symmetric cylindrical shell wall under the first-order shear deformation theory by the spline method, and analyzed the parameters of length, the number of circumferential nodes, the angle of the laminate, the number of laminates, the laminated material, and the boundary conditions of the anti-symmetric cylindrical shell. Baharali [ 21 ] studied the effects of carbon nanotubes (CNTs) and fiber carbon on the vibration frequency of anti-symmetric cylindrical shells, and evaluated the effects of carbon nanotube weight percentage and geometric parameters. Narwariya [ 22 , 23 ] conducted numerical studies on the free vibration and harmonic analysis of anti-symmetric laminates, and obtained the frequency-amplitude relationship of anti-symmetric anisotropic plates.…”
Section: Introductionmentioning
confidence: 99%
“…Applying different cycle times and vibration stress, Longbiao et al [3] analyzed the influences of composite properties and damage state on damping. Baharali et al [4] predicted the frequency of delaminated multi-scale composite shells based on an approximate-analytical solution. Qi et al [5] revealed increasing the fiber modulus can increase the frequency of the fiber-reinforced composite tube.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the outstanding advantages such as excellent corrosion resistance, good thermal insulation, the high stiffness, and low weight, some composite materials have been used to build reinforced thermoplastic pipes (RTPs) which can be used in the field of ocean engineering. [1][2][3][4][5] At present, RTPs have been successfully used as oil-gathering pipes, water injection pipes, and gas export pipes in the Middle East and Southeast Asia for many years. [6] As shown in Figure 1, RTPs consist of three main parts including the coating, laminates, and liner.…”
Section: Introductionmentioning
confidence: 99%